Pengaruh Pemberian Edukasi Skill Pertolongan Pertama Dan Peningkatan Pengetahuan Gawat Darurat Pada Remaja Dalam Penanganan Kecelakaan Lalu Lintas di Jombang - Permana, Arief; Bherty, Chanda (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: Increasing knowledge and first aid skills in traffic accidents is very important to be given an understanding in adolescence, the risk of accidents is quite high. First aid in emergencies is life support to prevent death to victims and prevent the occurrence of disabilities that may occur to the victim. The purpose of this research is to increase knowledge and skills in providing first aid to accident victims and unconscious victims independently. Methods: This research method uses Quasi Experimental in a cross sectional manner with one group pretest postest conducted on 26 adolescents in Puton Village, Diwek District, Jombang Regency. Knowledge was measured using a pre-test, knowledge questionnaire to adolescents and post-test after being given education related to emergency first aid skills in handling the risk of injury in traffic accidents Results: The results of the study after the implementation of the Wil-Coxon Sign Rank Test statistical test obtained the result of Pvalue = 0.0001 < α 0.05, this result indicates that Ho was rejected and Ha was accepted, namely there is an effect of providing education on emergency first aid skills in handling the risk of injury in traffic accidents on adolescents' knowledge about emergency first aid in Puton Village, Diwek District, Jombang Regency. Conclusion: There is an effect of providing education on emergency first aid skills in handling the risk of injury in traffic accidents on adolescents' knowledge about emergency first aid in Puton Village, Diwek District, Jombang Regency. Keywords: Knowledge, First Aid Skill Education, handling and prevention, Traffic accidents, Adolescents